Self-compatibility sources as sources of variation in advanced almond introgression lines - Gradziel T.M. (XVI GREMPA Meeting on Almonds and Pistachios, 2016)
Breeding for self-fruitfulness in almond requires the combination of pollen-pistil self-compatibility which is controlled by a single-major S gene and self-pollination or self-fertility which is controlled by multiple genes. Important sources for self-compatibility include Prunus webbii and its derivatives such as cv. Tuono which are pistil based, and peach and its wild relatives which are pollen based. The loci controlling the pistil and pollen self-compatibility genes are tightly linked which frustrates accurate Marker Assisted Selection. Methods of Marker Assisted Breeding complemented by Pedigree Based Analysis have facilitated the introgression of self-compatibility alleles from multiple independent sources including P. webbii, cv. ‘Tuono’, P. mira, and peach (P. persica). The final assessment of self-fruitfulness is determined by selfed-seed set in orchard trees where individual branches are enclosed to prohibit insect cross-pollination. The degree of self-fruitfulness under these field conditions has been found to be controlled by a major S-gene as well as modifier genes, often with significant environment interactions. In certain introgression lines, seedling tree age affects the expression of self-fruitfulness. Genetic background also strongly influences the level of self-fruitfulness as well as differences in branch architecture and so bearing habit. Some self-incompatible genotypes have also been found to express relatively high but inconsistent levels of self-fruitfulness. High levels of both expression and stability of self-fruitfulness is being pursued in advanced almond introgression lines by combining pistil-based and pollen-based genes with appropriate genetic backgrounds
16. Meeting of GREMPA (Groupe de Recherches Méditerranéennes pour l\'Amandier et Pistachier / Mediterranean Research Group for Almond and Pistachio), 2015/05/12-14, Meknes (Morocco)